2018
DOI: 10.3389/fncir.2018.00093
|View full text |Cite
|
Sign up to set email alerts
|

Auditory and Visual Motion Processing and Integration in the Primate Cerebral Cortex

Abstract: The ability of animals to detect motion is critical for survival, and errors or even delays in motion perception may prove costly. In the natural world, moving objects in the visual field often produce concurrent sounds. Thus, it can highly advantageous to detect motion elicited from sensory signals of either modality, and to integrate them to produce more reliable motion perception. A great deal of progress has been made in understanding how visual motion perception is governed by the activity of single neuro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 160 publications
1
15
0
Order By: Relevance
“…In literature, physiological evidence from single neuron studies of the primate cerebral cortex has suggested that the integration of visual and auditory motion cues may not be mediated by the early visual areas MT and MST and thus the integration likely occurs in higher-level cortical areas (Chaplin et al, 2018). Our finding that both primary and association visual and auditory inputs converge in L1 of the Pro suggests that the Pro is a region for the integration.…”
Section: Convergent Projections To Layer 1 Of the Promentioning
confidence: 55%
See 1 more Smart Citation
“…In literature, physiological evidence from single neuron studies of the primate cerebral cortex has suggested that the integration of visual and auditory motion cues may not be mediated by the early visual areas MT and MST and thus the integration likely occurs in higher-level cortical areas (Chaplin et al, 2018). Our finding that both primary and association visual and auditory inputs converge in L1 of the Pro suggests that the Pro is a region for the integration.…”
Section: Convergent Projections To Layer 1 Of the Promentioning
confidence: 55%
“…To our knowledge, this type of convergence was not reported previously. As recently discussed, L1 is an important hub for selectively integrating cortico-cortical and thalamocortical afferents (Chaplin et al, 2018). In L1, the excitation of apical dendrites of deep layer neurons by feedback projections as a way to amplify excitatory inputs to proximal dendrites may be a general mechanism used in cerebral cortex (Phillips, 2017).…”
Section: Convergent Projections To Layer 1 Of the Promentioning
confidence: 99%
“…The activations over this region have been proposed to subserve the comparison of sensory signals and to play an important role in perceptual tasks during which the comparison of the remembered and current stimuli has to be performed. Furthermore, subdivisions of this area (e.g., Brodmann area 8) are known to receive inputs from both motion pathway and auditory cortex (Romanski, 2007) and the PFC has been proposed to play a role in audiovisual motion integration recently (Chaplin et al, 2018).…”
Section: Temporal Disparity Level and (Right) Frontal Scalp Sitesmentioning
confidence: 99%
“…The analysis mechanism of motion direction in visual cortex differs from that of static contrast stimuli. Different neurons in the visual cortex can be activated by different directions of stimuli; this phenomenon is referred to as direction selectivity ( Tzvetanov, 2012 ; Chaplin et al, 2018 ). However, only a small number of neurons in the V1 area exhibit direction selectivity, although visual information from both eyes is transmitted to V1 at the first stage in primates ( Davies et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%